Pelatihan Dasar Pembuatan Merek Sebagai Identitas Produk UMKM Kelurahan Argasari - Rendy Sudirman; Heru Kurniawan; Ferryan Nugraha (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
Brands can be the strength of a product that is trusted by consumers. Micro, Small, and Medium Enterprises in Argasari Village, Cihideung District, Tasikmalaya City Basic Brand Making Training as a product identity has had an impact on Argasari Village business actors, totaling 28 people, as evidenced by the increase in the category of